Can professional football clubs deliver a weight management programme for women: a feasibility study - Christopher Bunn; Craig Donnachie; Sally Wyke; Kate Hunt; Graham Brennan; Jemma Lennox; Alice Maclean; Cindy M. Gray (BMC, 2018)
Abstract Background Levels of obesity remain high in the UK. The Football Fans in Training (FFIT) randomised controlled trial (RCT) demonstrated that a 12-week, gender-sensitised weight management, physical activity and healthy eating group programme delivered through professional football clubs helped men aged 35-65 years with BMI at least 28 kg/m2 lose a clinically-significant amount of weight. We aimed to test the feasibility of a minimally-adapted FFIT programme for delivery to women by assessing recruitment and completion rates; determining if the programme content and delivery required further refinement; and evaluating the potential of FFIT for Women to deliver improvements in weight and other clinical, behavioural and psychological outcomes. Methods A feasibility study of the FFIT for Women programme including before-and-after measurements of clinical (weight, waist, body mass index [BMI], blood pressure) behavioural (self-reported physical activity, food and alcohol intake) and psychological (self-esteem, positive and negative affect, physical and mental HRQoL) outcomes at five professional football clubs. Post-programme focus groups assessed acceptability of the programme format, content and style of delivery for women. Results Recruitment across the five clubs resulted in 123 women aged 35-65 years with BMI at least 28 kg/m2 taking part in the study. The mean weight (95.3 kg) and BMI (36.6 kg/m2) of the cohort were both suggestive of high risk of future disease. Of 123 women who started the programme, 94 (76%) completed it; 72 (58.5%) returned for 12-week follow-up measurements. Participants compared FFIT for Women favourably to commercial weight loss programmes and emphasised the importance of the programme's physical activity content. They also spoke positively about group dynamics, suggested that the approach to food was less restrictive than in other weight loss approaches, and broadly enjoyed the football setting. Mean weight loss was 2.87 kg (95% CI 2.09, 3.65, p ≤ 0.001). Mean waist reduction was 3.84 cm (2.92, 4.77, p ≤ 0.001). Conclusion In this evaluation, FFIT for Women was feasible, acceptable and demonstrated potential as a weight loss programme. Our findings suggest the programme has the potential to produce outcomes that are on a par with existing commercial and state-funded offerings.